PELAKSANAAN PEMBELAJARAN MUSIK TEKNOLOGI MENGGUNAKAN MODEL MANDIRI DI SMK NEGERI 7 PADANG - Pratama, Yudis; Irdhan Epria Darma Putra (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This research aims to describe the implementation of technology music learning using a self-study model in class XII Popular Music student of SMK Negeri 7 Padang. This research uses descriptive qualitative methods with data collection techniques in the form of observation, interviews, and documentation. The research result shows that implementation of technology music learning goes through three main stages, namely planning, monitoring, and evaluation. Planning is carried out through the preparation of modules and the selection of relevant learning resources. Monitoring is carried out with teacher assistance as well as student independent learning activities through the exploration of Cubase devices. Evaluation is carried out through the assessment of digital music works which include creativity, production techniques, and audio quality. The obstacles found include limited facilities and lack of practice hours at school. Overall, self-study can improve students’ ability in digital music production.